PERCEPTION OF ALUMNI ON HIGHER LEARNING EDUCATION EFFICACY IN BUTEMBO, DEMOCRATIC REPUBLIC OF CONGO (Proceedings of the International Conference on Future of Education, 2022)
This study analyzed the alumni perception of the educational efficacy of higher learning institutions in Butembo. A purposive sampling technique was used, and 281 respondents answered the survey of the study. Information was organized in tables for good interpretation. Results show that there are 31 Institutions for higher learning education in Butembo. Among them, InstitutSupérieurPédagogique de Muhangi (ISP-M) had 20.3% alumni among respondents, 12.3% were from InstitutSupérieur des Techniques Médicales (ISTM) Butembo, 11.0% of them from the Universté de l’Assomption au Congo (UAC), 9.6% from UniversitéCatholique du Graben (UCG), and 7.5% from UniversitéOfficielle de Ruwenzori. Findings reveal that graduates strongly agree that what they learned in college helps them in their profession. They agree that there are signs of higher learning institutions and universities' success in Butembo and surrounding, agreed to be satisfied by the training received. The findings show that workforce value is positively and significantly correlated with alumni's function (r=.883), with the education level (r=.806), with age (r=.745), current occupation (r=.718), gender of alumni (r=.598), operation activities (r=.549), and with the hierarchical position in the company (r=.465). Based on the findings, it was recommended that university students take their choice of orientation seriously for future education sustainability, career development, and community development by putting into practice what they learned during training.
Keywords: Perception of alumni; alumni; education efficacy; higher learning Institutions; Butembo